Avoiding the night terrors: the effect of circadian rhythm on post-operative urine output and blood pressure in free flap patients. Issue 5 (1st October 2021) - El-khayat, Bara; Foong, Deborah; Baden, James; Warner, Robert; Filobbos, George
Abstract: Multiple studies demonstrate the importance of goal-directed fluid regimens in avoiding complications. These regimens do not take account of circadian fluctuations in urine output (UO), MAP (mean arterial pressure) and pulse rate (PR). This is the first study that aims to demonstrate the effect of circadian rhythm on these haemodynamic parameters in post-operative patients with free flaps, as well as analysing clinicians' response to these variations. Retrospective analysis of 116 patients with free flaps. Records were assessed for UO, MAP, IV fluid infusion rate, oral fluid intake. Parameters were measured from 8 am to 8 pm (diurnal) and from 8 pm to 8 am (nocturnal) in the first 48 h post operatively. Patients with diabetes or hypertension were excluded. Mean diurnal UO rate (1.7 ml/kg/hr) was higher than nocturnal UO rate (0.7 ml/kg/hr); and mean diurnal MAP (93) was higher than nocturnal MAP (73.8). Mean diurnal IV infusion rate was 1.25 ml/kg/hr (lower) and mean nocturnal infusion rate 1.81 ml/kg/hr (higher). These differences were all statistically significant by paired student t -test ( p < 0.05). This study demonstrates that circadian rhythm has a statistically significant impact on UO, MAP and PR. UO, MAP and PR are expected to dip overnight. This dip is normal and does not necessarily need to be treated by increasing IV fluids to avoid over filling of free flap patients.